Service Quality and Word Of Mouth (WOM) Communication on Data Package Purchase Decisions: Kualitas Layanan dan Komunikasi Word Of Mouth (WOM) Terhadap Keputusan Pembelian Paket Data - Moch Yusuf Rizaldi Almuhtadibillah; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of Service Quality and Word of Mouth Communication (WOM) on purchasing decisions of data packages at Phe Honk Cell Ngampel Sari Candi Sidoarjo on Phe Honk Cell Ngampel Sari Candi Sidoarjo customers. This research method is descriptive quantitative. The population is Phe Honk Cell customers with the number of samples taken is 130 respondents. The sampling technique used was accidental sampling or accidental sampling. The analytical method used is multiple linear regression with reliability, validity, normality test, autocorrelation test, multicollinearity test, heteroscedasticity test, hypothesis testing, t test and F test, coefficient of determination with the help of SPSS version 20.0 program. The results showed that service quality and word of mouth (WOM) communication simultaneously had a positive and significant effect on purchasing decisions for data packages at Phe Honk Cell. But the service quality partially has no effect on purchasing decisions. Meanwhile, word of mouth (WOM) communication has a partial influence on purchasing decisions for data packages at Phe Honk Cell. Suggestions from the results of this study are that Phe Honk Cell can further improve, offer, and maintain Service Quality, so that customer trust in Phe Honk Cell is maintained and even increases. Highlights: The study examines the impact of service quality and word of mouth communication on purchasing decisions for data packages at Phe Honk Cell. Service quality and word of mouth communication together have a positive and significant influence on purchasing decisions. While service quality alone does not have a direct impact, word of mouth communication plays a partial role in influencing purchasing decisions. Keywords: Service quality, Word of mouth communication, Purchasing decisions, Data packages, Phe Honk Cell